Analisis Kesadaran Masyarakat Kelurahan Tegal Sari Mandala II dalam Pemanfaatan Air Bersih untuk Keperluan Rumah Tangga - Muhammad Najmul Fahmi; Mira Susila Warni; Nadratul Aini Lubis; Putri Anatasya Simanjuntak; Eni Yuniastuti (Lembaga Pengembangan Kinerja Dosen, 2025)
Clean water is a basic necessity that not only affects health but also social welfare and environmental sustainability. The aim of this research is to evaluate the level of public awareness in the Tegal Sari Mandala II sub-district regarding the use of clean water for household purposes and to identify the factors that influence public awareness in the utilization of clean water in the Tegal Sari Mandala II village. This research uses a qualitative approach with a descriptive evaluative method. Data in this study were collected through interview techniques, observation, and document studies, and analyzed using thematic analysis techniques. The results of this study indicate that community awareness in the Tegal Sari Mandala II sub-district is quite good, but the availability of clean water in this area is still limited due to the scheduling of PAM water distribution, which is from 8:00 AM to 4:00 PM, making it difficult for residents to meet their clean water needs for household use.